Avs Trigonometry Formulae

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 2

TRIGONOMETRIC FORMULAE

Fu Fun of θ Half angle formulae Fun of 2θ & 3θ

sin2 θ+ cos 2 θ=1 sin2 (θ/2)+ cos2 (θ /2)=1 2 tan θ


sin 2 θ=
1+ tan 2 θ
sin 2 θ=2 sin θ . cos θ sin θ=2sin (θ/2). cos(θ /2 ) 1−tan 2 θ
cos 2 θ=
1+ tan 2 θ
cos 2 θ=cos 2 θ−sin 2 θ cos θ=cos 2 (θ /2 )−sin 2 (θ/2 ) 2 tan θ
tan2 θ=
1−tan 2 θ
2
1+cos2θ = 2 cos θ
2
1+cosθ = 2 cos (θ /2) 2 tan( θ/ 2 )
sin θ=
1+ tan 2 ( θ / 2)
2 2
1-cos2θ = 2sin θ 1-cosθ = 2 sin (θ/2) 1−tan 2 (θ /2 )
cos θ=
1+tan 2 (θ/2 )
cos 2 θ=2 cos2 θ−1 cosθ=2 cos 2 (θ/2 )−1 2 tan ( θ/ 2)
tan θ=
1−tan 2 ( θ /2 )
cos 2 θ=1−2 sin2 θ cos θ=1−2 sin 2 (θ/2 ) 3
sin3θ = 3sinθ - 4sin θ
2 2
1+ tan θ=sec θ
2 2
1+ tan (θ /2 )=sec (θ /2) cos 3 θ=4 cos3 θ−3 cos θ
2 2 2 2
1+cot θ=cos ec θ 1+cot (θ/2 )=cos ec (θ /2) 3 tan θ−tan 3 θ
tan3 θ=
1−3 tan 2 θ
Compound Angle Formulae
Sin(A+B) = sinA.cosB + cosA.sinB Cos(A+B) = cosA.cosB – sinA.sinB

Sin(A-B) = sinA.cosB – cosA.sinB Cos(A-B) = cosA.cosB + sinA.sinB

tan A+tan B tan A−tan B


tan(A+B)= 1−tan A . tan B tan(A-B) = 1+tan A . tan B

Factorization and De-Factorization formulae

sinC + sinD =
2 sin
[ ] [ ]
C +D
2
.cos
C−D
2 2sinA.cosB = sin(A+B) + sin(A-B)

sinC – sinD =
2 cos
[ ] [ ]
C+ D
2
. sin
C−D
2 2cosA.sinB = sin(A+B) - sin(A-B)

cosC + cosD =
2 cos
[ ] [ ]
C+ D
2
. cos
C−D
2 2cosA.cosB = cos(A+B) + cos(A-B)

cosC – cosD =
−2 sin
[ ] [ ]
C+ D
2
.sin
C−D
2
- 2sinA.sinB = cos(A+B) – cos(A – B) OR
2sinA.sinB = cos(A – B) – cos(A + B)
INVERSE TRIGONOMETRIC FORMULAE

Prof. Shejwal A.V.


sin θ=1 /cos ec θ sin−1 x =cosec−1 (1/x )
cos ec θ=1 /sin θ cos ec−1 x=sin−1 (1/x )
cosθ=1 /sec θ cos−1 x=sec−1 (1/ x)
secθ=1 /cosθ sec−1 x=cos−1 (1/ x)
tanθ=1 /cot θ tan−1 x=cot−1 (1/ x )
cot θ=1 /tan θ cot−1 x =tan −1 (1/ x )
sin( 900 −θ)=cosθ sin( 900 +θ )=cosθ
cos(900 −θ )=sin θ cos(900 +θ)=−sin θ
tan(900 −θ )=cot θ tan(900 +θ )=−cot θ
sin(180 0−θ )=sinθ sin(180 0 +θ )=−sin θ sin(360 0 +θ )=sin θ sin(360 0−θ)=−sin θ
cos(1800 −θ )=−cosθ cos(1800 +θ )=−cosθ cos(3600 +θ)=cosθ cos(3600 −θ )=cosθ
tan(1800 −θ )=−tanθ tan(1800 +θ)=tan θ tan(3600 +θ)=tan θ tan(3600 −θ )=−tanθ

sin−1 (sin θ)=θ sin−1 (−x )=−sin−1 x

cos−1 (cosθ )=θ cos−1 (−x )=π −cos−1 x

tan−1 ( tan θ)=θ tan−1 (−x )=−tan−1 x

Sin(-θ ) = - sinθ Similar formulae for respective reciprocals

Cos(-θ ) = cosθ

Tan(-θ )=−tanθ

Prof. Shejwal A.V.

You might also like